The Availability of Leadership Skills Among General Managers and their Role in Achieving Organizational Integrity: An Analytical Study of the Opinions of a Sample of Managers in a Number of Directorates of the Ministry of Interior - Kurdistan Region of Iraq - Mohammed Murad, Zeravan; Ibrahim Wali, Ahlam (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The research sought to find out the availability of leadership skills in a number of directorates of the Ministry of Interior IN KRG represented by (human skills, technical skills, intellectual skills), on the dimensions of organizational integrity represented by (work regulations, principles and purpose, core values, organizational culture). The general framework of the research represented defining the problem by raising several questions about the availability of leadership skills and the nature of the relationship and the impact between them and achieving organizational integrity. For that, a hypothetical scheme was designed from which two main hypotheses emerged. key for data acquisition. The research followed the descriptive analytical approach, as the main and sub-variables were described, as well as the analysis of relationships and influence between the variables. The research community was represented by all managers in a number of directorates of the Ministry of Interior, and their number was (132) directors, while the sample was (80) directors. The two hypotheses were tested through a set of statistical tests using the computer program (SPSS V.23). The research reached a set of conclusions, the most important of which is the existence of high correlations and strong influences between the main and sub-variables, at the macro and micro levels, The research suggested a set of proposals in light of the conclusions, including the necessity of harnessing the strong relationships between the two variables and their orientation towards serving the surveyed directorates, with the need to strengthen the relationship between each of the leadership skills to achieve organizational integrity.